2008
DOI: 10.1128/mcb.01917-07
|View full text |Cite
|
Sign up to set email alerts
|

RalGDS Couples Growth Factor Signaling to Akt Activation

Abstract: The Akt kinase is a key regulator of cell proliferation and survival. It is activated in part by PDK1-induced phosphorylation. Here we show that RalGDS, a Ras effector protein that activates Ral GTPases, has a second function that promotes Akt phosphorylation by PDK1 by bringing these two kinases together. In support of this conclusion is our finding that suppression of RalGDS expression in cells inhibits both epidermal growth factor and insulin-induced phosphorylation of Akt. Moreover, while PDK1 complexes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 35 publications
(39 reference statements)
4
38
0
Order By: Relevance
“…2, C and D), indicating that insulin induces mTORC1 activation in a RalGDS-independent manner. Hao et al (36) recently reported that RalGDS forms a complex with PKB, a critical component in growth factor-regulated mTORC1 activation, and promotes PKB activation in breast cancer cell lines. We are not able to completely explain the conflict between those findings and the results of this study or the discrepancy in the requirement for RalA and RalGDS in insulin-induced mTORC1 activation.…”
Section: Resultsmentioning
confidence: 99%
“…2, C and D), indicating that insulin induces mTORC1 activation in a RalGDS-independent manner. Hao et al (36) recently reported that RalGDS forms a complex with PKB, a critical component in growth factor-regulated mTORC1 activation, and promotes PKB activation in breast cancer cell lines. We are not able to completely explain the conflict between those findings and the results of this study or the discrepancy in the requirement for RalA and RalGDS in insulin-induced mTORC1 activation.…”
Section: Resultsmentioning
confidence: 99%
“…Another explanation for the crucial role of Rgl2 in PDAC transformation is isoform-specific Ral-independent functions, because Rgl2 has been shown to interact with the Ras scaffolding protein CNK (43), whereas RalGDS interacts with PDK1 to promote AKT activation (20,52). In line with this hypothesis is our observations that Rgl2 knockdown and RalA31N expression strongly suppressed anchorage-independent growth in MIA PaCa-2 without suppression of RalA activity and that in MIA PaCa-2 cells, activated RalA was not able to rescue the anchorage-independent growth phenotype of Rgl2 knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, depletion of Rgl2 may disrupt the ability of CNK to promote Raf signaling. Another possible mechanism is based on the demonstrated ability of RalGDS to activate AKT in a Ral-independent manner (20). To address these mechanisms, we determined if Rgl2 depletion corresponded with reduced AKT and/or ERK activity levels.…”
Section: Rgl2 Overexpression In Pdac Tumors-thementioning
confidence: 99%
See 1 more Smart Citation
“…Akt kinases are the most important PI3K effector molecules. Studies of both transformation (11,20,21) and cell death (22) have focused attention on Akt. Translocated to membranes by stimulation of PI3K signaling, Akt is activated by phosphorylation at Thr-308 by PDK1 (PI3K-dependent protein kinase 1) (23) and at Ser-473 by the mTORC2 complex (24).…”
mentioning
confidence: 99%